Material Montessori y motricidad fina en los niños de 4 a 5 años, Unidad Educativa Marieta de Veintimilla, ciudad de Loja, período 2023-2024 - Valarezo Duchicela, Daniela Maribi (2024)
Fine motor skills are a complex process that requires the participation of various cortical areas, coordinating neurological, skeletal, and muscular functions, that is, it allows both hands and wrists to perform firm and precise movements to carry out actions in a harmonious way, holding or grasping objects, necessary for the control of sight and manipulation of the materials you want to reach. The research was aimed at determining if the Montessori material influences fine motor skills in children from 4 to 5 years old, Marieta de Veintimilla Educational Unit, in the city of Loja, implementing a mixed approach, descriptive scope and quasi-experimental design that allowed collecting information analyzing the study and characteristics of the variables; the inductive-deductive, analytical-synthetic methods contributed to the construction of the theoretical framework and the analysis of the information to reach general conclusions; the Batelle Development Inventory, designed for children from 0 months to 8 years of age, was used to verify the difficulties they presented in the subareas of fine motor and perceptual motor skills when copying figures, crumpling paper, opening a lock, cutting with scissors, following a line and tying a knot, where 68% of the children investigated were at the retarded and low level at the beginning of the research. After applying the activity guide based on the Montessori material, it was noted that 80% of the children achieved a normal level. The researcher concludes that the use of Montessori material as a methodological strategy favors the area of fine motor skills, being an effective resource for the development of hand-eye coordination, muscle tone, greater pincer precision and the acquisition of significant learning, increasing the essential skills for good writing. Key words: Motor coordination, concrete material, tactile precision, muscle tone.